"Mon respe tou lezot lalang!": a case study of native teacher attitudes towards Creole-mediated multilingual education in Seychelles*. Issue 2 (3rd April 2018) - Fleischmann Schwarz, Christina Tamaa; Nick, I. M.
ABSTRACT: In January 1982, the Republic of Seychelles became the first country to make its Creole, Seselwa, an official medium of instruction in its multilingual education system. Overall, this innovative language policy has positively affected student levels of personal motivation and academic success. Nevertheless, the nation's continued use of Creole-mediated multilingual education (CMME) has not been without critics. Chief among them have been the expected purveyors of the CMME policy – teachers. Using a mixed-method survey research design, this study investigated teacher attitudes towards the nation's three official languages: Seselwa, English, and French; and the Seychelles' CMME policy. The overall research result was as sobering as it was clear. Despite the government's 30-year commitment to CMME, the majority of the teachers polled still questioned the efficacy of this policy. Importantly, as this investigation demonstrates, a primary source of this doubt may be found in the teachers' own language profiles. The implications of these research findings for the future of CMME in Seychelles are discussed and recommendations for future investigations of vernacular instruction are presented.